(untitled) (International journal of artificial intelligence, 2026)
This article explores the role of artificial intelligence in personalized English language learning. In particular, it analyzes the capabilities of AI-based educational platforms in providing adaptive learning approaches tailored to learners’ individual needs and abilities. The study theoretically examines the significance of artificial intelligence in increasing learner motivation, supporting independent learning, and enhancing the overall effectiveness of the learning process.